2022
DOI: 10.1242/jcs.258929
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative regulation of adherens junction expansion through epidermal growth factor receptor activation

Abstract: The mechanisms controlling the dynamics of expansion of adherens junctions are significantly less understood than those controlling their static properties. Here, we report that for suspended cell aggregates, the time to form a new junction between two cells speeds up with the number of junctions that the cells are already engaged in. Upon junction formation, the activation of the Epidermal Growth Factor Receptor (EGFR) distally affects the actin turnover dynamics of the cell-free cortex. The “primed” actin co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…[14][15][16] . For example, cadherin recruitment leads to biochemical and biophysical modulation of cortical properties via various Rho GTPases [16][17][18] . In turn, cortical tension drives the mechanosensitive recruitment of cadherins at adherens junction 15 .…”
Section: Decoupling Actin Cortex Properties From Binder Recruitmentmentioning
confidence: 99%
“…[14][15][16] . For example, cadherin recruitment leads to biochemical and biophysical modulation of cortical properties via various Rho GTPases [16][17][18] . In turn, cortical tension drives the mechanosensitive recruitment of cadherins at adherens junction 15 .…”
Section: Decoupling Actin Cortex Properties From Binder Recruitmentmentioning
confidence: 99%
“…We previously reported that E-cad-dependent phosphorylation of EGFR in suspended cell doublets increases the velocity of de-novo junction formation 8 and the toughness of their adhesion 16 . In all cases, the microscopic dynamics of the actin cortex are associated with a change in cell deformability, with minimal impact on cortical tension.…”
Section: Mainmentioning
confidence: 99%
“…While viscous dissipation in the actin network is commonly regarded as a constant passive parameter in cell migration in both 2D and 3D contexts, there is limited knowledge concerning the regulation of dissipative forces arising from viscous drag between cells during collective rearrangement. Here, we found that the phosphorylation of Epithelial Growth Factor Receptor (EGFR) downstream of de novo E-cadherin adhesion 7, 8 orchestrates a feedback loop, thereby governing intercellular viscosity via the Rac pathway regulating actin dynamics. Our findings highlight how the E-cadherin-dependent EGFR activity controls the migration mode of collective cell movements independently of intercellular tension.…”
mentioning
confidence: 99%
See 1 more Smart Citation